External Validation and Comparison of Two Nomograms Predicting the Probability of Lymph Node Involvement in Patients subjected to Robot-Assisted Radical Prostatectomy and Concomitant Lymph Node Dissection: A Single Tertiary Center Experience in the MRI-Era - Frego, Nicola; Paciotti, Marco; Buffi, Nicolò Maria; Maffei, Davide; Contieri, Roberto; Avolio, Pier Paolo; Fasulo, Vittorio; Uleri, Alessandro; Lazzeri, Massimo; Hurle, Rodolfo; Saita, Alberto; Guazzoni, Giorgio Ferruccio; et al. (Frontiers in Surgery, 2022)
Introduction To externally validate and directly compare the performance of the Briganti 2012 and Briganti 2019 nomograms as predictors of Lymph Node Invasion (LNI) in a cohort of patients treated with Robot-Assisted Radical Prostatectomy (RARP) and extend Pelvic Lymph Node Dissection (ePLND). Materials and Methods After exclusion of patients with incomplete biopsy, imaging or clinical data, 752 patients who underwent RARP and ePLND between December 2014 to August 2021 at our center, were included. Of these 327 (43.5%) had undergone multi parametric Magnetic Resonance Imaging (mpMRI) and mpMRI-targeted biopsy. The preoperative risk of LNI was calculated for all patients using Briganti 2012 nomogram, while the Briganti 2019 nomogram was used only in patients who had performed mpMRI with the combination of targeted and systematic biopsy. The performance of Briganti 2012 and 2019 models were evaluated using the area under the receiver-operating characteristics curve analysis, calibrations plot and decision curve analysis. Results A median of 13 (IQR 9-18) nodes per patient were removed, and 78 (10.4%) patients had LNI at final pathology. The AUCs for Briganti 2012 and 2019 were 0.84 and 0.82, respectively. The calibration plots showed a good correlation between the predicted probabilities and the observed proportion of LNI for both models, with a slight tendency to underestimation. The DCAs of the two models were similar, with a slightly higher net benefit for Briganti 2012 nomogram. In patients receiving both systematic- and targeted-biopsy, the Briganti 2012 accuracy was 0.85, and no significant difference was found between the AUCs of 2012 and 2019 nomograms (p = 0.296). In the sub-cohort of 518 (68.9%) intermediate-risk PCa patients, the Briganti 2012 nomogram outperform the 2019 model in term of accuracy (0.82 vs. 0.77), calibration curve and net benefit at DCA. Conclusion The direct comparison of the two nomograms showed that the most updated nomogram, which included data on MRI and targeted biopsy, was not significantly more accurate than the 2012 model in the prediction of LNI, suggesting a negligible role of mpMRI in the current population.